Beneficial and unsafe plant species within selected grazing areas in Bomet County: HABITAT Project – Harnessing Pasture Biodiversity and Productivity - Matheka, Kennedy W.; Leitner, Sonja; Kinuthia, Kelvin (International Livestock Research Institute, 2024)
Why a high number of different plant species is vital for fodder Grazing areas with a high variety of fodder plants can improve forage yield, and different plants provide different levels of nutrients to livestock at various stages during their growth cycles. In addition, a high diversity of plants can protect natural habitats and pastures from the invasion of weeds and invasive plant species. And the more different plants occur in a given area, the more the likelihood of improving soil fertility and reducing the need for use of fertilizers or pesticides